MEMBANGUN SISTEM PENJUALAN TEMPLATE E-STORE BERBASIS WEB DENGAN PHP DAN MYSQL - Farida, Eni; Wahid Efendi, Ahmad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
E-store template is a simple sales systems that run the web based online. E-store is almost the same as e-commers who have been circulating on the internet but the e-store is more simple and suitable for businessmen who developed the business. While the template is one of the web system to facilitate maintenance of the web itself. Based on observations at the web address (site), which operates in the same field, most of the web address of the web has not set prices affordable by the community. Hopefully this simple application can be a solution for entrepreneurs to expand their business and hopefully the price offered for this web more affordable by the community. Â Keywords : Template Sales System E-store